2018
DOI: 10.3389/fonc.2018.00043
|View full text |Cite|
|
Sign up to set email alerts
|

Melanoma Unknown Primary Brain Metastasis Treatment with ECHO-7 Oncolytic Virus Rigvir: A Case Report

Abstract: Melanoma is considered an aggressive malignancy with a tendency of forming metastasis in the brain. Less than 10% of all melanoma cases present with unknown primary tumor location. This diagnose is yet to be fully understood, because there are only theoretical assumptions about the nature of the disease. Melanoma brain metastases have many severe side effects and, unfortunately, any disease related to the brain has limited therapeutic options due to the blood–brain barrier. The course of the disease after a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Rigvir as a monotherapy and in combination with other therapies has also been tested in patients for whom the prognosis is especially poor. One patient with a basal cell carcinoma, a diagnosis with a median expected survival of five months, was treated with Rigvir post-surgery [101]. The treatment regime began with daily injections for three days, graduating step-wise to thrice-weekly for multiple years.…”
Section: Echovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigvir as a monotherapy and in combination with other therapies has also been tested in patients for whom the prognosis is especially poor. One patient with a basal cell carcinoma, a diagnosis with a median expected survival of five months, was treated with Rigvir post-surgery [101]. The treatment regime began with daily injections for three days, graduating step-wise to thrice-weekly for multiple years.…”
Section: Echovirusesmentioning
confidence: 99%
“…The treatment regime began with daily injections for three days, graduating step-wise to thrice-weekly for multiple years. At the time of publication, the patient’s condition has been stable for 3.9 years, with scans showing minimal residual metastasis [101]. Another study documented Rigvir treatment of a stage IV poorly-differentiated rectal adenocarcinoma, with a 5-year survival rate of 5% [102].…”
Section: Echovirusesmentioning
confidence: 99%
“…The problem of a lack of studies is even more evident in the subgroup of BM-CUP due to the rarity of cases, unfavourable prognosis, and frequent exclusion from clinical trials. Therefore, most information on innovative treatments comes from case reports [ 65 , 71 , 72 , 73 , 74 ]. Even if anecdotal, these reports offer good insight on feasible therapeutic strategies and potentially successful treatments in this rare and fatal disease ( Table 5 ).…”
Section: Managementmentioning
confidence: 99%
“…However, there is no histological record available confirming the basal cell carcinoma diagnosis. In contrast, immunohistochemistry showed that the tumor cells were weakly positive for HMB-45 and Melan A, strongly positive for MART-1, S-100 and vimentin, and that the Ki-67 index was 35% [7].…”
mentioning
confidence: 78%
“…However, the registered mode of administration of Rigvir is intramuscular [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
mentioning
confidence: 99%